Context-aware privacy and security agents for distance education. (3rd April 2006) - Yee, George; Korba, Larry; Lin, Nigel H.; Shih, Timothy K.
Although distance education applications have been widely deployed, not many of them provide privacy and security for their users. Most of them only provide access control by requesting a user id and password. In a recent paper for AINA (Lin et al., 2004), we conveyed the importance of privacy and security for distance education and showed how they can be provided. In this paper, we present an extension of that work for the use of context-aware agents that can provide privacy and security for distance education applications in an intelligent manner based on the user's interaction context. Our agents are based on an agent framework adapted from IEEE P1484.1/D9: the Learning Technology Systems Architecture (LTSA) (IEEE, 2004).